2016
DOI: 10.1016/j.msea.2016.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pores on crack initiation in monotonic tensile and cyclic loadings in lost foam casting A319 alloy by using 3D in-situ analysis

Abstract: Lost Foam Casting (LFC) process is replacing the conventional gravity Die Casting (DC) process in automotive industry for the purpose of geometry optimization, cost reduction and consumption control. However, due to lower cooling rate, LFC produces in a coarser microstructure that reduces fatigue life. In order to study the influence of the casting microstructure of LFC Al-Si alloy on damage micromechanisms under monotonic tensile loading and Low Cycle Fatigue (LCF) at room temperature, an experimental protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 21 publications
2
65
0
Order By: Relevance
“…Such unmelted zones are observed in the bulk or in sub-surface areas. As the position of the defects respectively to the surface is an influencing parameter on the crack initiation time, as shown in the case of shrinkage in casting alloys [4,5], this has an impact on the criticality and the lifetimes. In the case of unmelted zones, one can observe in Figure 3 that the fatigue properties are qualitatively slightly better for the specimens built in the XY direction.…”
Section: Discussion and Comparison With Casting Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…Such unmelted zones are observed in the bulk or in sub-surface areas. As the position of the defects respectively to the surface is an influencing parameter on the crack initiation time, as shown in the case of shrinkage in casting alloys [4,5], this has an impact on the criticality and the lifetimes. In the case of unmelted zones, one can observe in Figure 3 that the fatigue properties are qualitatively slightly better for the specimens built in the XY direction.…”
Section: Discussion and Comparison With Casting Processesmentioning
confidence: 99%
“…In fact, in the case of casting alloys, it has been shown that a simple 2D analysis (size, morphology) from data extracted from surface images of such complex 3D defects is generally not sufficient to understand and quantify their impact on crack initiation mechanisms and on lifetime, even if some statistical corrections are possible [11]. Therefore, a systematic 3D quantitative analysis of the specimens microstructure by CT-tomography (as conducted in [6]) could be a direct perspective of this work, associated to in-situ fatigue tests as in [4,5].…”
Section: Discussion and Comparison With Casting Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the local crack propagation law was extracted from the kinematic measurements [132]. Likewise, crack initiation was observed in cast aluminum alloy with kinematic and residual fields [234]. Short fatigue cracks were analyzed in cast magnesium alloy with the measured bulk displacement fields [147].…”
Section: Introductionmentioning
confidence: 99%